2012
DOI: 10.1017/s0033291712002012
|View full text |Cite
|
Sign up to set email alerts
|

Neurological soft signs in obsessive-compulsive disorder: two empirical studies and meta-analysis

Abstract: Background. Neurological soft signs (NSS) have been inconsistently reported in obsessive-compulsive disorder (OCD) but may make an impact on treatment response.Method. The current study examined the presence of NSS in two independent European samples of OCD patients (combined 85 patients and 88 matched healthy controls) using a standardized instrument and conducted a metaanalysis of all published studies identified in the literature with the aim to provide a more definitive answer to the question of whether OC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 56 publications
(117 reference statements)
0
27
1
1
Order By: Relevance
“…It would be of interest to test whether antiadrenergic agents (e.g., clonidine or prazosin) might moderate the NSSs observed here. However, the reversibility of NSSs is questionable [39], given that this has only been found in some [104] but not in all OCD patients [105][107], and not in patients with bipolar disorder [108] or schizophrenia [107], [109]. In sum, resolution of the risk factor vs. acquired origin interpretation of the observed NSSs in PG, as well as NSSs' possible response to treatment and/or their ability to predict [37], [110] such a response (as has been shown for OCD patients) will require prospective clinical trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be of interest to test whether antiadrenergic agents (e.g., clonidine or prazosin) might moderate the NSSs observed here. However, the reversibility of NSSs is questionable [39], given that this has only been found in some [104] but not in all OCD patients [105][107], and not in patients with bipolar disorder [108] or schizophrenia [107], [109]. In sum, resolution of the risk factor vs. acquired origin interpretation of the observed NSSs in PG, as well as NSSs' possible response to treatment and/or their ability to predict [37], [110] such a response (as has been shown for OCD patients) will require prospective clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to hard neurological signs localizable to a specific brain site, their soft counterparts are attributed to wider brain regions and functionally connected neuroanatomical systems, involved in integrative neurological functions such as sensory perception, coordination and motor sequencing [32], [33]. Neurological soft signs have been observed in a growing number of neuropsychiatric syndromes including mood disorders [34][36], obsessive-compulsive disorder (OCD) [37][39], post-traumatic stress disorder [26], [27], impulse control disorder [40], schizophrenia [32], [34], [41], and attention deficit hyperactivity disorder [42]. Furthermore, an inverse relationship between NSSs scores and total brain volume has been noted in psychopathological populations [27], [43] adding support to the generalized rather than localized NSSs' nature.…”
Section: Introductionmentioning
confidence: 99%
“…Second, although all subjects in the SCH group were medicated, there is not a consensus regarding the influence of medication on NSSs. Kolakowska et al concluded that the higher prevalence of NSSs found in schizophrenia patients could not be attributed to medication (Kolakowska et al, 1985) and a recent meta‐analysis indicated that NSSs were independent of medication effects (Jaafari et al, 2013). On the other hand, two research groups have reported correlations between NSSs and neuroleptic medication dosage and/or extrapyramidal side‐effects (Youssef and Waddington, 1988; King et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of studies assessing NSS in adults with OCD suggested significantly higher rates compared to matched controls, present bilaterally and in multiple domains (motor coordination, sensory integration, and primitive reflexes). [81] These subtle neurologic abnormalities may characterize subgroups of patients with more severe symptoms[82] and poorer treatment response. [83] In children, deficits in visuospatial and fine-motor skills based on neuropsychological testing may also predict poor long-term outcomes.…”
Section: Clinical Assessmentmentioning
confidence: 99%